Activity and selectivity of Mg-Fe mixed oxides in the aldol condensation of furfural - Kocík, Jaroslav; Kikhtyanin, Oleg; Tomášová, Adéla; Smoláková, Lucie; Hájek, Martin; Čapek, Libor (My University, 2016)
The aim of this work has been to compare the activity and selectivity of Mg-Fe mixed oxides in the aldol condensation of furfural with that of previously studied Mg-Al mixed oxides. Mg-Fe mixed oxides were prepared by thermal pre-treatment of hydrotalcites with a Mg/Fe molar ratio from 1.1 to 7.6. Structural and textural properties of Mg-Fe mixed oxides were analysed by using of XRD and N2-adsorption. It was found that Mg-Fe mixed oxides exhibited lower conversion of furfural in contrast to the Mg-Al mixed oxides, but being more selective to 4-(2-furyl)-3-buten-2-one (FAc). The difference in the conversion of furfural was relatively low among the Mg-Fe mixed oxides with the Mg/Fe molar ratio in the range of 1.1-5.5.
Aktivita a selektivita směsných oxidů Mg-Fe v aldolové kondenzaci furfuralu
Keywords: catalytic activity; Mg-Fe; mixed oxides; aldol condensation; furfural; katalytická aktivita; Mg-Fe; směsné oxidy; aldolová kondenzace; furfural